(untitled) (Вісник: Міжнародні відносини, 2024)
The article aims to analyse the current state and future prospects of humanitarian cooperation between Ukraine and Poland against the background of Russia’s fully-fledged aggression. The call for the formation of a unified Ukrainian-Polish cultural and informational space as a tool for countering the Russian expansionist and imperial space in the course of the cognitive warfare is emphasised. Moreover, the authors 86 argue that in addition to the significant intensification of cooperation between Kyiv and Warsaw in the military and political, military and technical, economic and financial domains, humanitarian cooperation between these neighboring countries will become one of the drivers of the European integration of Ukraine. The research acknowledges the increasing mutual interest in the study of languages, cultures and traditions of the Ukrainian and Polish peoples, the reinvigoration of cooperation in the educational and media fields, the development of cultural and public diplomacy.